Systematic Fusion of Multi-Source Cognitive Networks With Graph Learning - A Study on Fronto-Parietal Network - Zhang, Xiaofei; Yang, Yang; Kuai, Hongzhi; Chen, Jianhui; Huang, Jiajin; Liang, Peipeng; Zhong, Ning (Frontiers in Neuroscience, 2022)
Cognitive tasks induce fluctuations in the functional connectivity between brain regions which constitute cognitive networks in the human brain. Although several cognitive networks have been identified, consensus still cannot be achieved on the precise borders and distribution of involved brain regions for each network, due to the multifarious use of diverse brain atlases in different studies. To address the problem, the current study proposed a novel approach to generate a fused cognitive network with the optimal performance in discriminating cognitive states by using graph learning, following the synthesization of one cognitive network defined by different brain atlases, and the construction of a hierarchical framework comprised of one main version and other supplementary versions of the specific cognitive network. As a result, the proposed method demonstrated better results compared with other machine learning methods on recognising cognitive states, which was revealed by analysing an fMRI dataset related to the mental arithmetic task. Our findings suggest that the fused cognitive network provides potential to develop new mind decoding approaches.